Interplay of Murine Gammaherpesvirus 68 with NF-kappaB Signaling of the Host - Cieniewicz, Brandon; Santana, Alexis L.; Minkah, Nana; Krug, Laurie T. (Frontiers in Microbiology, 2016)
Herpesviruses establish a chronic infection in the host characterized by intervals of lytic replication, quiescent latency, and reactivation from latency. Murine gammaherpesvirus 68 (MHV68) naturally infects small rodents and has genetic and biologic parallels with the human gammaherpesviruses (gHVs), Kaposi’s sarcoma-associated herpesvirus and Epstein-Barr virus. The murine gammaherpesvirus model pathogen system provides a platform to apply cutting-edge approaches to dissect the interplay of gammaherpesvirus and host determinants that enable colonization of the host, and that shape the latent or lytic fate of an infected cell. This knowledge is critical for the development of novel therapeutic interventions against the oncogenic gHVs. The NF-κB signaling pathway is well-known for its role in the promotion of inflammation and many aspects of B cell biology. Here, we review key aspects of the virus lifecycle in the host, with an emphasis on the route that the virus takes to gain access to the B cell latency reservoir. We highlight how the murine gammaherpesvirus requires components of the NF-κB signaling pathway to promote replication, latency establishment, and maintenance of latency. These studies emphasize the complexity of gammaherpesvirus interactions with NF-κB signaling components that direct innate and adaptive immune responses of the host. Importantly, multiple facets of NF-κB signaling have been identified that might be targeted to reduce the burden of gammaherpesvirus-associated diseases.